O-3 Facilitating successful implementation of a person-centred approach to carer assessment and support. Issue Volume 6: Issue (2016)Supplement 1 (1st November 2016) - Diffin, Janet; Ewing, Gail; Grande, Gunn
Abstract : Background: The Carer Support Needs Assessment Tool (CSNAT) intervention identifies and addresses family carer support needs towards end of life. This person-centred approach involves a change in practice from a practitioner – to carer-led assessment process. Numerous policies recommend carers' needs should be addressed yet there is little guidance on how to achieve this within palliative care. To address this gap and assist a change to a carer-led process, an implementation strategy for the CSNAT intervention was developed, of which facilitation is key. Aims: Investigate components of facilitation associated with successful implementation of the CSNAT intervention across a range of palliative/end-of-life care services. Methods: Qualitative: Interviews three and six months post-CSNAT implementation with 38 practitioners with the role of CSNAT 'champion' (internal facilitation) in 32 services. Researcher field notes collected from teleconference support sessions with 'champions' (external facilitation). Results: Successful implementation of the CSNAT intervention was associated with: utilising a teamwork approach to facilitation; the 'lead champion' having a leadership role in the service e.g. team manager; presenting a clear rationale why a change in practice was needed; reviewing progress and making changes to overcome identified barriers; 'champions' having good communication skills and authority to make changes. Larger services faced more barriers to facilitation e.g. difficulties with providing training to all staff and less frequent opportunities to review progress as a team. Aspects of context which constrained facilitation included the need to establish a new carer record, and organisational changes e.g. budget cuts, and a culture focused on the patient. In contrast, support from management was one aspect of context which assisted with facilitation efforts. Conclusions: In addition to managerial support, establishing a team of practitioners to lead facilitation of the CSNAT intervention and regularly review implementation progress, is vital for implementation success. This study was funded by Dimbleby Cancer Care.